Assessing the level of economic consciousness and the level of health consciousness of the COVID-19 pandemic: Evidence from Indonesia - Alini, Alini; Harahap, Dewi Anggriani; Irfan, Andi; Febria, Dessyka (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Nowadays, the issue of the COVID-19 pandemic is very shocking to the world, it has altered the pattern of human life toward a new life order. This new life order requires the consciousness of every human being. AIM: The aim of this study was to assess health consciousness and economic consciousness of the risk of being exposed to COVID-19. The hypothesis indicated that the level of economic consciousness was higher than the level of health consciousness during the COVID-19 pandemic. METHODS: The research method used was a quantitative method using surveys and it was complemented by direct interviews with respondents. RESULTS: The finding based on the economic level found that people with uncertain income were more concerned with economic consciousness than health consciousness. Besides, the societies with uncertain income, especially non-formal workers, were not so afraid of the coronavirus 19 and they did not care while contracting the virus, due to they have believed that life and death have been determined by God. Other results showed that respondents worked as small traders, medium and large entrepreneurs were also more concerned with economic consciousness rather than health consciousness, it revealed that the societies did not have regular income and they argued that COVID-19 was merely an ordinary virus. CONCLUSION: Respondents who were employees, health workers and other professions who had regular income, they tended to pay more attention to health consciousness than economic consciousness due to these societies had sufficient savings if they selected the quarantine at home.